Ontogenetic shape changes and sexual dimorphism in Aegla marginata Bond-Buckup and Buckup, 1994 - ADAM,CAROLINA L. (2018)
ABSTRACT A study on relative growth, sexual dimorphism and ontogenetic trajectory was carried out in a population of the aeglidAegla marginata coming from Barrinha River, Iguape River Basin, Tunas do Paraná, Paraná State, Brazil. The size the of morphological sexual maturity was estimated for males and females. The analysis of sexual dimorphism and ontogenetic trajectory were performed using geometric morphometric technique. Males reach maturity with 10.58 mm of carapace length (CL) and females with 10.38 mm CL. Sexual size dimorphism was only visible among adults, with males reaching larger sizes. This is probably related to the reproductive strategy of males. However, sexual shape dimorphism was found for both juveniles and adults: the posterior region of the carapace was wider in females. As the contrast of this feature was stronger in adults, it can be considered that large abdomen is advantageous for egg incubation. The allometric trajectories of juveniles presented similar directions, becoming divergent during the adult phase. The shape variation inA. marginataoccurred gradually throughout its development, with no abrupt transformation upon reaching sexual maturity. The reproductive adaptation is the main reason for the morphological variation within populations ofA. marginata.